Analysis Of The Influence Of Company Performance Value On Stock Price - Masno Marjohan (Program Pascasarjana STIE Amkop Makassar, 2023)
The purpose of the research is to test and analyze the significance of the influence of Economic Value Added, Debt to Equity Ratio, Return on Equity, and Total Asset Turnover on Stock Prices in companies listed on the Indonesia Stock Exchange. This research method uses secondary data. The sample in this study was determined by the purposive sampling technique. The samples used in this study were 8 (eight) companies listed on the Indonesia Stock Exchange. Hypothesis testing using panel data regression analysis tools with the help of Eviews software. The results of this study indicate that Economic Value Added, on Stock Price is not influential, and Return On Equity there is an influence but not significant on Stock Price. Debt to Equity Ratio and Total Asset Turnover have a significant effect on Stock Prices and Simultaneous variables of Economic Value Added, Return On Equity, Debt to Equity Ratio, and Total Asset Turnover simultaneously and significantly affect Stock Prices in property and real estate sector companies. Keywords: Economic Value Added; Debt to Equity Ratio; Return on Equity; Total Asset Turnover and Stock Price